The Mummy of Aleksander Fredro from the Fredro Chapel in the Parish Church in Rudki Near Lwów - Promińska, Elżbieta (Anthropological Review, 1992)
The mummy of Aleksander Fredro from the Fredro Chapel in the Parish Church in Rudki near Lwów was examined in 1988 by the committe established by the Ministry of Culture.